(untitled) (The Review of Diabetic Studies, 2024)
Background: Benign prostatic hyperplasia (BPH) is a prevalent condition in older men, causing significant morbidity. Benign prostatic hyperplasia can lead to urinary retention, and often the presence of moderate-to-severe lower urinary tract symptoms could impact on patients’ quality of life. Aim: to assess the relation between the severity of lower urinary tract symptoms and quality of life among patients with benign prostatic hyperplasia. Research design: A descriptive correlational research design was utilized. Setting: Saudi University Hospital, Urology department. Sample: A targeted sample of sixty male patients with BPH who were experiencing lower urinary tract symptoms. Tools: tool I: A structured interview questionnaire, tool II: International Prostate Symptom Score, tool III: Benign prostatic hyperplasia - Specific Quality of life scale. Results showed that the mean age of studied patients was 51.97±4.94 years. 80% presented with grade II, according to severity of lower urinary tract symptoms, 3.30% had mild symptoms, 71.0 % had moderate symptoms, and 25.0% had severe symptoms. There was a statistically significant positive correlation between the severity of lower urinary tract symptoms and quality of life (P. value <0.01) Conclusion: The quality of life among patients with benign prostatic hyperplasia decreases with the increment in the severity of their lower urinary tract symptoms. Recommendation: Further studies are needed to study factors aggravating the severity of lower urinary symptoms among patients with benign prostatic hyperplasia and target interventions that burden its effect on patients’ quality of life.